HUMANISM IN PESANTREN; HERMENEUTICAL ANALYSIS OF MONOTHEISM IN THE BOOK OF UMM AL-BARÄ€HÄªN - Anwar, Adnan Nuril (Journal of Islamicate Studies, 2019)
Humanitarian problems are global issues that seem to have never been thoroughly discussed. Indonesia, as one of the democratic countries that uphold human values, is not immune to the humanitarian problems that often arise among the people. How not, contemporary situations that imply various forms of repression of humanity (discrimination, intimidation of beliefs, restrictions, and restrictions on religious activities, expressions of hatred in the name of religion, etc.), require Islamic theological discourse which is widely studied in the world of pesantren to take a role in building progressive discourse that can answer the problems of religious life. In this regard, this article seeks to address the issue of the extent to which the interpretation of Islamic theological discourse, especially the knowledge of Tawheed, can provide a deeper understanding of humanitarian issues. To fulfill this goal, this paper will examine the commentary and the meaning of the phrase Tawheed in the book of Umm al-BarÄhÄ«n. By using the hermeneutical-analysis method, this paper finds that the Tawheed sentence contains important ideas about humanity which are the ontological basis for the creation of horizontal relationships (hablun min al-nÄs) that are following the meaning of the Tawheed sentence, including the principle of unity, equality, justice, tolerance, and democracy. In connection with these principles, pesantren have an important role in implementing the meanings of the phrase Tawheed in social life so that it can be understood and lived back contextually that pacifies and reconciles religious life in Indonesia.